Preference erosion: The case of Bangladesh. A SUR-EC-AR gravity model of trade - Erika Vianna Grossrieder (Graduate Institute of International Studies, 2007)
This paper analyses the impact of preference erosion on Bangladesh's clothing industry coming from both the ATC quotas phasing-out and the reduction on MFN tariffs under NAMA negotiations. First, it undertakes a numerical exercise to estimate the effects of tariffs reduction in the US and the EU on Bangladesh's economic performance. Then it uses a SUR-EC-AR gravity model of trade to measure the effects of ATC quotas phasing out and NAMA negotiations on trade pattern. The results suggest that Bangladesh gains from importing countries' tariffs reduction, independently of ATC implementation. Despite the fact that these results may underestimate the effects of quotas phasing out on T&C trade pattern, the model's structure presents the advantage of eliminating the aggregation bias problem. It would be interesting to expand the econometric model to include other trade partners and new variables.
Keywords: 330; Zollpräferenzen; Importquote; Handelseffekt; Textil- und Bekleidungsindustrie; Außenhandelsstruktur; Gravitationsmodell; Schätzung; Bangladesch